Institutional Complexity of Civil Service Reforms in Pakistan: Challenges and Impediments - Madiha Rehman Farooqui; Dr. Yaamina Salman; Dr. Zafar Iqbal Jadoon; Prof. Dr. Nasira Jabeen; Dr. Sidra Irfan (Journal of Political Studies, 2019)
Over the last two decades, there is an increasing trend of structural reforms in the administrative system of South Asian countries. In this region, the traditional bureaucratic model of public administration prevails in retrospection of colonial and postcolonial periods (Haque, 2003). The new agenda is to transform the traditional public sector model with business-like practices in line with the current global movement for such a transition. The central theme of this paper revolves around the institutional complexity faced by public sector organizations in line with institutional pressures. It also explicates how organizations respond to the complexity created by multiple and conflicting logics. This paper explores institutional complexity of federal training institutions of Pakistan by investigating the way these organization adopted the new proposed logic of civil service reforms. It describes how new management practices are introduced in training institutions and how well they are interpreted and adopted by these organizations. This study is based on 18 semi structured interviews from the senior and middle line management of federal training institutions. Participants are purposively selected as unit of observation and data is analyzed by using thematic analysis. In this regard, this study presents a scientific insight to federal training institutions and their adoption of market logic. Cultural institutional perspective has appeared to have high explanatory power to explain this phenomenon. This paper argues that organizational characteristics like size, its position in the field, its legal entity, and its linkages with the ministry are important determinants while studying relationships between complexity and organizational responses. The paper recommends further empirical research on the current topic by linking organizational responses to institutional complexity to organizational outcomes and to contextualize these findings in other settings.